The relationship between providing health videos and knowledge of pregnant women in the Covid-19 era at the Sedayu II Health Center in Yogyakarta - Noviyani Noviyani; Fatimah Fatimah; Taufik Rahman; Lia Dian Ayuningrum; Amanah Rahma Delia (Alma Ata University Press, 2022)
Background : Pregnant women and their fetuses are a priority for high-risk populations during an outbreak of an infectious disease. Pregnancy will naturally cause a decrease in the immune system, especially during the Covid-19 pandemic which can cause excessive anxiety, stress, and exposure to corona virus infection. Several studies state that the use of smartphones has high effectiveness as a medium for health education because they can convey information through audiovisuals, have high portability, and have applications that support improving the quality of health services. Previous research has shown that pregnant women still have a low understanding of Covid-19 prevention regarding efforts to prevent COVID-19 infectionObjectives : The purpose of providing health education through videos to pregnant women is to increase knowledge about covid in pregnancyMethods : in this study, the population was all trimester I, II, and III pregnant women who performed ANC at the Sedayu II Health Center in June 2020, totaling 30 pregnant women. Provided educational videos which were sent via WhatsApp to each respondent. The pretest and posttest were sent via Google form and data analysis used the Wilcoxon test.Results : Research shows that there is a significant relationship between providing educational videos about pregnancy and the knowledge of pregnant women about Covid-19 in Bantul. Health education using videos and online utilization is the main choice during the COVID-19 pandemic to prevent increased morbidity and mortality of mothers and newborns.Providing educational videos is considered effective because health workers can still provide KIE to patients by avoiding direct contact to prevent transmission of the corona virus. Pregnant women can be guided to learn about pregnancy and childbirth through MCH books. All of these approaches can contribute to a comfortable pregnancy, reduced risk of infection, better preparedness for labor, maternal experience, postpartum adjustment and outcomes, and greater economic benefits for the health system and the pregnant woman herself. Conclusions : The results of this study indicate that the use of online video-based educational media is recommended as an alternative method and is considered very appropriate for use during a pandemic